Peran Psikoedukasi dalam Meningkatkan Efektivitas Pengelolaan Sekolah Inklusi di SDIT X Bekasi Utara - Perdini, Tiara Anggita; Indrawati, Erdina; Pertiwi, Yuarini Wahyu (Jurnal Kajian Ilmiah, 2024)
Inclusive education is the social responsibility of educational institutions to ensure that every child, including children with special needs, receives an equal education. However, the challenges faced in implementing inclusive education, especially in the effectiveness of learning for ABK students, show a significant academic gap. Although there are accompanying teachers for each ABK student, many of them still have difficulty understanding the subject matter due to the lack of teacher competence in handling students with special needs. This research method uses interview assessment, observation, and Focus Group Discussion (FGD) to analyze the management of inclusive education at SDIT X. The results of the assessment showed that the lack of special training for accompanying teachers and the inadequacy in understanding the characteristics of ABK students resulted in suboptimal support. Therefore, improvements are needed in the inclusive education system by using psychoeducational interventions. The results obtained were an increase in understanding from teachers and parents regarding how to handle ABK students, and gradually they began to implement this knowledge in daily practice.